PENGARUH PROGRAM DANA BERGULIR OLEH UPK DAN TENAGA KERJA TERHADAP PENINGKATAN PENDAPATAN KUWA DI DESA BAMBANG KECAMATAN TURI LAMONGAN - Evi Fitrotun Najiah; Yunni Rusmawati DJ (STIE Mahardhika, 2018)
There are three PNPM-MPd programs in Turi Subdistrict namely the first in physical form where this assistance focuses on the development of both infrastructure and facilities that can have an impact to facilitate the community in carrying out activities that support economic activities in the area and in activities this community will be accompanied by technical facilitators. Whereas the second activity is in the form of training in which the proposed community or group will be trained to form a productive group which can later form an independent business group and is expected to have a positive impact on improving the economy for this activity. the third is in the form of savings and loans which in this activity people will become partners with UPK (Activity Management Unit) this activity is a special savings and loan group of women formed from a group of women who have businesses both livestock business, design and craft they form the group and applying for a loan at UPK aim to improve and develop the business that is run. the objectives in this study include: to determine the effect of partially the UPK revolving fund program and the workforce on increasing the income of KUWA in Bambang Village, Turi Lamongan Subdistrict, to determine the simultaneous effect of UPK revolving fund program and workforce on increasing KUWA income in Bambang Village Turi Lamongan Subdistrict and to find out which variable has the most dominant influence on the increase of KUWA income in Bambang Village, Turi Lamongan District. From the results of the study there are the results of the regression coefficients of each independent variable, namely the revolving fund program (X1) = 0.449 and Labor (X2) = 0.004, so it can be concluded that the most dominant factors affecting income increase (Y) are factors of the Revolving Fund Program by UPK (X1).